THE QURANIC HERMENEUTICS APPROACH TO GENDER EQUALITY IN AMINA WADUD MUHSIN’S VIEW - Yusuf, Muhammad; Baharuddin, Baharuddin; Mardan, Mardan (Jurnal Adabiyah, 2020)
Gender is a social construction of what is called masculine and feminine and the division of social roles. Hermeneutics is an alternative approach to understand the Qur'anic text. This study aims to analyze Amina Wadud's hermeneutics of interpreting the texts of the Qur'an on gender issues. The data presented comes from the references from a variety of relevant sources—the method of critical analysis conducted to explore Amina Wadud. Personal, family, intellectual, and cultural background cannot be separated from her thoughts on gender issues. He said that there were no truly objective interpreters. Indirectly, she was included in the statement. Therefore, she proposed a holistic method to reduce excessive interpreter subjectivity in understanding texts, especially gender issues. The Hermeneutics stands on the analysis of language, history, and contextualization. Amina's hermeneutics is influenced by the thoughts of Fazlur Rahman and Gadamer. الجندر هو بناء اجتماعي لما يسمى الذكوري والأنثوي وتقسيم الأدوار الاجتماعية. التأويل هو منهج بديل لفهم النصوص القرآنية. تهدف هذه الدراسة إلى تحليل تأويلات أمينة ودود لتفسير نصوص القرآن في قضايا النوع الاجتماعي. وتأتي البيانات المقدمة من المراجع المتنوعة ومن مجموعة متنوعة من المصادر ذات الصلة - طريقة التحليل النقدي التي أجريت لاستكشاف أمينة ودود. لا يمكن فصل الخلفية الشخصية والعائلية والفكرية والثقافية عن أفكارها حول قضايا النوع الاجتماعي. وقالت إنه لم يكن هناك مفسرون موضوعيون حقا. وبغير مباشرة ، كانت هي في تلك الحالة. لذلك، اقترحت طريقة شاملة للحد من الذاتية المفرطة للمفسرين في فهم النصوص، وخاصة قضايا الجنسين. يقف علم التأويل على تحليل اللغة والتاريخ والسياق. تتأثر تأويلات أمينة بأفكار فضل الرحمن وجادامر. Gender merupakan konstruksi sosial dari apa yang disebut maskulin dan feminin serta pembagian peran sosial. Kajian tentang isu gender seringkali merujuk kepada posisi perempuan yang tersubordinasi atau sebaliknya, menempatkan perempuan melampau kodratnya. Bagaimana cara memposisikannya di tempat yang tepat? Penelitian ini bertujuan untuk menganalisis hermeneutika Amina Wadud dalam menafsirkan teks Alquran tentang isu gender. Data yang disajikan berasal dari berbagai sumber yang relevan — metode analisis kritis yang dilakukan untuk mendalami ide Amina Wadud. Ia menegaskan bahwa latar belakang pribadi, keluarga, intelektual, dan budaya tidak lepas dari pemikirannya tentang isu gender. Selain itu, tidak ada penafsir yang benar-benar objektif. Secara tidak langsung, dia termasuk dalam pernyataan penafsir yang tidak benar-benar objektif. Ia mengusulkan metode holistik untuk meminimalisir subjektivitas dan egoisme penafsir yang berlebihan dalam memahami teks, khususnya masalah gender. Hermeneutika berdiri di atas analisis bahasa, sejarah, dan kontekstualisasi. Hermeneutika Amina dipengaruhi oleh pemikiran Fazlur Rahman dan Gadamer.